The experience of the limit or the failure of the human: A philosophical anthropology against the backdrop of the sacred-profane dialectic - Groza, Elvira (Journal for the study of religions and ideologies, 2021)
The text aims to analyze modes of subjectivation in the context of the meta-experience of the sacred-profane dialectic, particularly in the context of the full concealment of the sacred in the profane. The authors start from the hypothesis of the revelation of an irreducible ontological structure of the human, which is the experience of the paradoxical limit between aformal and formal. Consequently, the endeavor of the authors is structured as a way of confirming their hypothesis through: 1) analysing the specificity of Eliade’s anti-reductionist approach as a historian and philosopher of religions and his openness towards anthropology; 2) the application of phenomenology and hermeneutics in order to show Eliade’s research scheme: facts - forms - symbolical structures - existential structures; 3) explaining the experience of the paradoxical limit between the sacred and the profane as a structure of the human; 4) inventorizing the human structures and the modes of subjectivation generated by the irreducibility of the experience of the paradoxical limit; 5) a brief account of the reinterpretation of the experience of the limit as a structure of the humanity in contemporary phenomenological writings. The authors consider that the experience of the paradoxical limit between the sacred and the profane, the miracle and the ordinary, is irreducible, and the proof is the interpretation of that limit in contemporary philosophical works in the form of: sovereignty (Georges Bataille), self-affection of Life (Michel Henry), or desire of the self through the other (Renaud Barbaras). The hypothesis of the experience of the limit or of the transformation of the man in the limit as a structure of the human is confirmed, as well as the interpretation of that limit by Eliade as coincidentia oppositorum.